НАУКОВО-ПЕДАГОГІЧНА СПАДЩИНА В. О. СУХОМЛИНСЬКОГО У ПРОЦЕСІ ФОРМУВАННЯ ОСОБИСТОСТІ ВЧИТЕЛЯ-СЛОВЕСНИКА - Каліш, Валентина; Собко, Валентина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття присвячена проблемі підготовки вчителя-словесника до реалізації пріоритетних напрямів сучасної мовної освіти. Йдеться про готовність майбутнього вчителя забезпечувати формування мовної особистості школяра, починаючи з початкової ланки, що значною мірою залежить від рівня професійно-педагогічної компетентності майбутнього фахівця. Одним із аспектів вирішення означеної проблеми є використання у процесі формування особистості сучасного вчителя-словесника спадщини відомого педагога В. О. Сухомлинського – видатної української мовної особистості. Статья посвящена проблеме подготовки учителя-словесника к реализации приоритетных направлений современного языкового образования. Речь идет о готовности будущего учителя обеспечивать формирование языковой личности школьника, начиная с начального звена, что в значительной мере зависит от уровня профессионально-педагогической компетентности будущего специалиста. Одним из аспектов решения этой проблемы является использование в процессе формирования личности современного учителя-словесника наследия известного педагога В. А. Сухомлинского – выдающейся украинской языковой личности. The article is devoted to the issue of training a linguist teacher to the implementation of the priority directions of modern language education. The paper deals with an intending teacher’s readiness to provide forming a pupil’s language personality, beginning from primary school that mostly depends on the level of professional and pedagogical competence of an intending specialist. One of the aspects of solving the mentioned problem is the using famous educator V. O. Sukhomlynsky’s heritage – prominent Ukrainian language and literature personality – in the process of forming a personality of a modern linguist teacher. The recommendations for using V. Sukhomlynsky’s works, as didactic material for mastering linguistic knowledge and skills by intending specialists, forming a pedagogue specialist, a practicing teacher that can project cultural and educational environment and successfully implement their knowledge, creativity, professional skills it in, are given in the article.